Design and Build Training Need Analysis Application Parahita Diagnostic Center Laboratory Surabaya - Effendi, Pradita Maulidya; Supriyanto, Antok; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Parahita Diagnostic Center (PDC) provides the aim of improving the quality of service becomes faster, more convenient, and accurate on the basis of human resources (HR) is competent. Sumber Daya Insani (SDI) & Umum is part assigned to training for all employees PDC. Based on identification and analysis of problems, SDI & Umum has a problem in the process of determining the training needs for assessment competence test has not shown effective results. Impact, time to analyze customer samples will be long and causing delays lab results. This resulted in the PDC service quality to decrease. To overcome these problems, then made application solutions competency-based training needs analysis. This application can analyze the value of the results of competency tests to generate the amount of tolerance gap on the type and level of competence. Analysis of the gap tolerance can be seen priority training needs for each employee. Based on the results of the implementation and evaluation of systems, applications have suitability between the results of calculations using the application with using manual calculations. The application obtained the information gap that training needs are categorized by level knowledge, skill, and attitude.